Gut microbiota and metabolic profiles in adults with unclassified diabetes: a cross-sectional study - Zhang, Juan; Wu, Lei; Zhang, Zhongyun; Li, Danjie; Han, Rulai; Ye, Lei; Zhang, Yifei; Hong, Jie; Gu, Weiqiong (Frontiers in Endocrinology, 2024)
Aims: Our study, employing a multi-omics approach, aimed to delineate the distinct gut microbiota and metabolic characteristics in individuals under 30 with unclassified diabetes, thus shedding light on the underlying pathophysiological mechanisms.Methods: This age-and sex-matched case-control study involved 18 patients with unclassified diabetes, 18 patients with classic type 1 diabetes, 13 patients with type 2 diabetes, and 18 healthy individuals. Metagenomics facilitated the profiling of the gut microbiota, while untargeted liquid chromatography-mass spectrometry was used to quantify the serum lipids and metabolites.Results: Our findings revealed a unique gut microbiota composition in unclassified diabetes patients, marked by a depletion of Butyrivibrio proteoclasticus and Clostridium and an increase in Ruminococcus torques and Lachnospiraceae bacterium 8_1_57FAA. Comparative analysis identified the combined marker panel of five bacterial species, seven serum biomarkers, and three clinical parameters could differentiate patients with UDM from HCs with an AUC of 0.94 (95% CI 0.85-1). Notably, the gut microbiota structure of patients with unclassified diabetes resembled that of type 2 diabetes patients, especially regarding disrupted lipid and branchedchain amino acid metabolism.Conclusions: Despite sharing certain metabolic features with type 2 diabetes, unclassified diabetes presents unique features. The distinct microbiota and metabolites in unclassified diabetes patients suggest a significant role in modulating glucose, lipid, and amino acid 3 metabolism, potentially influencing disease progression. Further longitudinal studies are essential to explore therapeutic strategies targeting the gut microbiota and metabolites to modify the disease trajectory.